Building a Literate and Character-Oriented Generation through Cultural Narratives: A Community-Based Literacy Program in Rejoyoso Village, Malang - Hapsari, Dyah Eko; Wulandari, Istiqomah; Purwaningtyas, Isti; Fatimah, Fatimah (Faculty of Cultural Studies, Universitas Brawijaya, 2026)
This community service program, organized by the lecturers and students of the Faculty of Cultural Studies, Universitas Brawijaya, in collaboration with KCC Galeri Kreatif, was designed to strengthen children’s cultural literacy through several strategic activities. First, a children’s literature workshop for volunteers focused on enhancing their competence in assisting children with reading stories in creative and interactive ways. Second, a creative writing training for children was conducted to encourage them to express reflections on noble values found in children’s literature through poems, short summaries, and simple visual works. Third, a literacy festival served as a space for appreciation and expression, where children showcased their literary works through folktale reading, storytelling, poetry recitation, and exhibitions of reflective creations. Finally, the management of a mini library was carried out by organizing the collection by genre and implementing simple cataloging to provide structured access to reading materials. Altogether, these programs are expected to foster reading interest, strengthen cultural literacy, and cultivate children’s creativity within a community-based learning ecosystem.